Attendance System with Near Field Communication Web-based and IoT - Eggi Julian; Yayan Cahyan (STMIK Sumedang, 2021)
The application and implementation of student attendance conventionally using paper media in universities, especially STMIK Sumedang has several problems, including disruption of the lecture process with circulars of absent documents, students often taking advantage of loopholes and working together with other students to commit fraud, for example, students who attend classes. class, often sign the attendance of friends who are not present in lectures, then there is the possibility of damage and loss of absent documents, the occurrence of human errors in the process of recapitulating attendance data, and the amount of time wasted using this method and the difficulty of quickly and accurately getting attendance data for evaluation needs which are running. Attendance for lecturers is not much different from students because it is still done conventionally. The fingerprint-based employee attendance has several weaknesses, such as the possibility of employees forgetting to do a finger scan at the beginning of work or the end of work, the absence of details of the work carried out by employees during working hours. This study offers a solution to overcome these problems, namely by designing a Web-based application that can record attendance data more easily with an attendance intermediary device with a microcontroller-based IoT. The method used is the waterfall, the steps taken include the method of collecting data on the current system, identification and analysis of system and user requirements, system design based on studies, designed with the PHP programming language and MySQL database with the addition of Laravel Framework and Vue.js as application formation. The proposed. The Internet of Things (IoT) microcontroller is used as a reader and sender of data for validation that is integrated into the system. The test is planned to be carried out using the simulation method from several data from students, lecturers, employees, and course schedules so that it can be used as a reference for monitoring and evaluating the performance of the Academic.